TWO NEW SPECIES OF PARAMYLONCHULUS AND DESCRIPTION OF MONONCHUS TRUNCATUS BASTIAN, 1965 FROM MANIPUR - DHANACHAND, CH.; ROMABATI, N.; ANANADI, Y. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Paramylonchulus japanicus n.sp. and Paramylonchulus cassicus n.sp. are collected from the soil around the roots Japanese grass and Cassia fistula respectively in Manipur state. P. japanicus n.sp. is distinctive in having narrowerlin narrower and shorterbuccal cavity, shorter uterine sac, spicule, gubernaculum and more ventromedian supplements. cassicus n. sp. is characterized by its shape and size of buccal cavity, shorter uterine sac, absence of sphincter, shorter gubernaculum, in the nature of tail, more ventromedian supplements and tandem caudal glands. One known species Mononchus truncatus Bastian, 1965 has also been recorded for the first time in India.